Review of sustainable alternatives for the use of orange marc - Dávila, Tatiana Liceth Alvarado; Hernández Sierra, Alba Teresa (Revista Colombiana de Investigaciones Agroindustriales, 2018)
Orange waste is produced in large quantities worldwide and must be managed properly to avoid contamination in water, land and air, and other natural resources. The composting technique of orange waste is a conditioning factor during the degradation process due to its physicochemical and microbiological features, there is a high moisture content, acidity, low decomposition and the presence of essential oils that delay the compost process. According to the literature review where different treatments are analyzed for transforming orange waste into composting; it was found a record of investigations developed with methods such as forced aeration by manual dumping, outdoors, addition hydroxide of calcium, agro industrial waste, pruning waste, urban waste, cows’ dung and other type of techniques such as the production of biofuels and / or the extraction of essential oils. The study showed that it is possible to reduce the environmental impact on orange waste through composting technique by pre-treating dehydration or the extraction of pectin and D-limonene in order to optimize the decomposition time; as well as improving the physical and chemical microbiological conditions of the compost. It is also important to note that another option to take advantage of citrus is through the reconversion of waste to industrial processing, biogas or bioethanol to obtain new products.